Potential of Indigenous Microorganisms (IMO) from cow manure, elephant grass, Aloe vera, pineapple skin to the N, P and K content of organic cow manure. Issue 1 (November 2021) - Novia, D; Sandra, A; Yogi, A; Allismawita,; Putra, A A
Abstract: The manufacture of organic fertilizers can be accelerated by adding indigenous microorganisms (IMO) which function as decomposers. The purpose of this study was to determine the effect of adding several types of IMO to the N, P, and K content of organic cow manure. This research used animal MOL, namely cow manure IMO and vegetable IMO, namely elephant grass IMO, Aloe vera IMO, pineapple skin IMO and dry cow manures. This study used an experimental method with a completely randomized design with five treatments and four replications. The treatments were A: addition of cow manure IMO, B : elephant grass IMO, C : Aloe vera IMO, D : pineapple skin IMO, E : combination IMO (A, B, C, D). The parameters were measured; the N, P and K content. The results showed that the addition of several types of IMO had a significant effect (P<0.05) on phosphorus content of organic cow manure but had no significant effect (P>0.05) on nitrogen and potassium content. The manufacture of organic cow manure with the addition of several types of IMO for 21 days gave the best results in the combination IMO treatment with 1.70% nitrogen, 0.65% phosphorus, and 1.78% potassium content.